Outcomes of Hospitalized COVID-19 Patients by Risk Factors: Results from a United States Hospital Claims Database - Peter J. Mallow; Kathy W. Belk; Michael Topmiller; Edmond A. Hooker (Journal of Health Economics and Outcomes Research, 2020)
**Background/Objective:** The primary objective was to quantify the role of the number of Centers of Disease Control and Prevention (CDC) risk factors on in-hospital mortality. The secondary objective was to assess the associated hospital length of stay (LOS), intensive care unit (ICU) bed utilization, and ICU LOS with the number of CDC risk factors. # Methods A retrospective cohort study consisting of all hospitalizations with a confirmed COVID-19 diagnosis discharged between March 15, 2020 and April 30, 2020 was conducted. Data was obtained from 276 acute care hospitals across the United States. Cohorts were identified based upon the number of the CDC COVID-19 risk factors. Multivariable regression modeling was performed to assess outcomes and utilization. The odds ratio (OR) and incidence rate ratio (IRR) were reported.